Anti-microbial activity of rooibos tea (Aspalathus linearis) on food spoilage organisms and potenial pathogens - Schepers, Sonette (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2001.